Concentrations of levonorgestrel and ethinylestradiol in wastewater effluents: Is the progestin also cause for concern?. (18th March 2016) - King, Olivia C.; van de Merwe, Jason P.; McDonald, James A.; Leusch, Frederic D.L.
Abstract: Synthetic hormones have been widely reported in treated sewage effluents, and consequently receiving aquatic environments. Ethinylestradiol (EE2) is a potent synthetic estrogen commonly used in conjunction with levonorgestrel in oral contraceptive pills. Both EE2 and levonorgestrel have been identified in the aquatic environment, but although there is a significant amount of literature on EE2, there is much less information on levonorgestrel. Using Australian prescription data as well as excretion and predicted wastewater removal rates, the concentrations of EE2 and levonorgestrel in Australian wastewater were calculated at 0.1 ng/L to 0.5 ng/L and 0.2 ng/L to 0.6 ng/L, respectively. Both compounds were analyzed in treated wastewater and surface water grab samples from 3 Southeast Queensland, Australia sites. The predicted no‐effect concentration (PNEC) for EE2 of 0.1 ng/L was exceeded at most sites, with EE2 concentrations up to 2 ng/L in treated effluent, albeit quickly diluted to 0.1 ng/L to 0.2 ng/L in the receiving environment. A provisional PNEC for levonorgestrel of 0.1 ng/L derived in the present study was slightly lower than predicted effluent concentrations of 0.2 ng/L to 0.6 ng/L, indicating a potential risk of endocrine‐related effects in exposed aquatic species. The detection limit for levonorgestrel in the present study was 2.5 ng/L, and all samples were below detection limit. The present study's results suggest that improvements in analytical capabilities for levonorgestrel are warranted to more accurately quantify the risk of this compound in the receiving environment. Environ Toxicol Chem 2016;35:1378–1385. © 2015 SETAC